2017
DOI: 10.3390/cancers9060059
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes in Patients with CRC: The Role of Patient Reported Outcomes—An ESDO Report

Abstract: Colorectal cancer is one of the most commonly diagnosed cancers worldwide and nearly half of patients will develop metastatic disease at some point during the course of their disease. The goal of anticancer therapy in this context is to extend survival, while trying to maximise the patient’s health-related quality of life. To this end, we need to understand how to incorporate patient-reported outcomes into clinical trials and routine practice to accurately assess if treatment strategies are providing clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Indeed, most studies reviewed the evidence that the communication processes in health systems are complex. PROs incorporation in oncology improves clinical practice [ 42 , 47 , 92 ], structures the communication, develops effective communication tools and communication skills training [ 93 95 ], and contributes to the delivery of effective oncology high-quality care [ 34 , 39 , 76 ], improved patient-safety and patient satisfaction, and reduces patient anxiety [ 39 , 42 , 48 , 49 , 65 67 , 77 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, most studies reviewed the evidence that the communication processes in health systems are complex. PROs incorporation in oncology improves clinical practice [ 42 , 47 , 92 ], structures the communication, develops effective communication tools and communication skills training [ 93 95 ], and contributes to the delivery of effective oncology high-quality care [ 34 , 39 , 76 ], improved patient-safety and patient satisfaction, and reduces patient anxiety [ 39 , 42 , 48 , 49 , 65 67 , 77 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…identified key areas of improvement and confirmed that well-conducted and reported prognostic model studies with a PRO predictor have great potential to improve healthcare delivery [ 38 ]. The physical functioning, global health and QoL domains were consider significant prognostic factors (prognosticators) and several domains have been evidenced [ 39 , 40 , 43 ] including patient-reported functional scores [ 37 , 42 , 60 , 61 , 63 , 68 ], patient-reported symptom interference [ 38 , 49 , 59 , 62 , 65 , 66 ], patient-reported depression [ 96 ], or patient-reported fatigue [ 67 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These measure are known as patient reported outcomes (PROs). PROs allow for early detection of distress in a patient, provides a valuable opportunity for patients to be heard, and allows for interventions to be directed toward specific symptoms (43). Thanks to new psychometric techniques and electronic platforms, much of this data can now be easily collected.…”
Section: Introductionmentioning
confidence: 99%